University legitimacy and student compliance with academic dishonesty codes: a partial test of the process-based model of self-regulation - Reisig, Michael Dean (Criminal justice and behavior, 2016)
This study tests whether behavioral intentions to commit two forms of student academic dishonesty (i.e., cheating on exams and plagiarizing a paper) are related to perceived university legitimacy. Cross-sectional data from a university-based sample (N = 502) are used to construct a three-dimensional, second-order confirmatory model of university legitimacy. The results from the ordinal logistic models show that students who perceive university authority as legitimate are less likely to express intentions to cheat on an exam, net of other known correlates of deviance and demographic factors. This finding holds when the Legitimacy Scale is disaggregated. When it comes to plagiarism, the effect of university legitimacy is null. Overall, the findings indicate that the explanatory scope of the process-based model extends rule breaking beyond criminal justice settings and that university authorities can curb student cheating by ensuring that their processes and procedures used to manage students are evenhanded.